PELATIHAN KELOMPOK SADAR WISATA (POKDARWIS) MELALUI KEGIATAN TATA KELOLA DESTINASI PARIWISATA DI KAB SERANG - chotibul umam umam; Dadang Suganda; Ute Lies Siti Khadijah; Evi Novianti; Mukti Utama (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Serang Regency consists of 326 villages. The existence of villages has the potential for tourist attractions such as nature, culture, culinary and creative economy, but most of the villages have not used them as tourist destinations. Therefore, the community plays an important role in utilizing and managing tourist attractions, one of the institutions at the village that is engaged in tourism is the Tourism Awareness group (Pokdarwis), which acts as a motivator and communicator in an effort to increase the readiness and awareness of the community around the tourist attraction. Training activities aimed at Pokdarwis throughout Serang Regency in order to strengthen knowledge about Tourism Destination Management. The training method are presentation, Forum Group Discussion (FGD), brainstorming and evaluation. The results of this training are expected that pokdarwis have knowledge and be able to implementation in their village.